(3eYGde GdOjf hedGP GdeLJgOjfs - (3GdYGedj, GdTGej, CHh efUhQ, Gf GdTgjO GdKGfj, GdMSf Hf Rjf GdOjf Hf Ydj Hf CMeO, J (B1011 (3g`s
(3ChdgG (B:s
.. (3hCe GdJbOe ehVhYg Ch dJbOe ZGjJg Ch dGTJeGdg Ydi eHGOF GdYdhe GdeJCNQI Ch dZjQ Pdc ef GdChQ GdJj djS gPG ehVY PcQgG heQJHI gPG GdYde eJCNQI Yf ZjQg HGdGYJHGQ GdKGdK (B...s
(3BNQgG (B:s
... (3jQLY Edjg GdebdO eY GdGLJgGO Cf jchf eDefG YOdG haj UMI QLhY GdebdO Edjg Ydeg HMUhd GdTQGFW ajg EeG deNGdWI GdeWdYI Ch HGdCNHGQ GdeJhGJQI (B...s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B2\192s
(3GdPQjYI (B21\4595s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3CUhd Gdabgs